Protective or harmful? A qualitative exploration of older people’s perceptions of worries about falling - Ellmers, Toby J; Wilson, Mark R; Norris, Meriel; Young, William R (Age and ageing, 2022)
Abstract Background worries about falling are common in older people. It has been suggested that these worries can reduce balance safety by acting as a distracting dual-task. However, it is also possible that worries may serve a protective purpose. The present work adopted a qualitative approach to conduct an in-depth exploration of older people’s experiences of worries about falling. Methods semi-structured interviews were conducted with 17 community-dwelling older people (mean age = 79 years; males = 5/17) who reported experiencing worries about falling. Reflexive thematic analysis was used to analyse the data. Results experiencing a fall—or otherwise recognising one’s balance limitations—brought the physical realities of participants’ ageing bodies to the forefront of their awareness. This led to the recognition of their susceptibility for an injurious fall, which triggered worries about falling in situations that threatened their balance. When preventing the subject of their worries (i.e. an injurious fall) was perceived to be within the individual’s locus of control, worries led to protective adaptations to behaviour. In contrast, when the subject of their worries was perceived to be outside their control, worries triggered feelings of panic—leading to unhelpful changes in behaviour. Conclusion these findings provide novel insight into the development and consequences of worries about falling in older people. They highlight the importance of considering an individual’s perception of control before deciding to clinically intervene to reduce worries about falling.